The Impact of Continued Mekong Basin Hydropower Development on Local Livelihoods - Pearse-Smith, Scott William David (Consilience, 2012)
Hydropower development of the Mekong Basin is proceeding at an increasingly rapid pace. Hydropower has already affected the natural and social environments of the Mekong, and threatens to cause further devastation for local livelihoods as hydropower projects increase in size and number. This article builds upon scientific knowledge of the environmental effects of Mekong hydropower development to consider what impacts these environmental changes will have on local livelihoods. Attention is focused on how hydropower development will affect crucial renewable resources, and how this will affect the production of food and income for millions of the basin’s inhabitants. This study contends that the food and economic security of the majority of the local population is inextricably intertwined with the integrity of the natural environment. Therefore, continued hydropower development will have a devastating impact on the livelihoods of millions of the basin’s inhabitants. More sustainable alternatives are desperately required.